Air quality biomonitoring through Olea europaea L.: The study case of "Land of pyres". (November 2021) - Guarino, Francesco; Improta, Giovanni; Triassi, Maria; Castiglione, Stefano; Cicatelli, Angela
Abstract: The "Land of pyres", namely "La Terra dei Fuochi", is an area of Campania region (South-Italy), highly inhabited and comprises between the Provinces of Naples and Caserta, sadly known worldwide for the criminal activities related to the illegal waste disposal and burning. These fires, concomitantly with traffic emissions, might be the source of potential toxic element (PTE) dangerous for the human health and causing pathologies. In the framework of Correlation Health–Environment project, funded by the Campania region, eight municipalities (of area "Land of pyres") and three remote sites have been bio-monitored using the olive ( Olea europaea L.) plants as biomonitors. Leaves of olive plants were collected in each assayed municipality and the concentration of 11 metal(loid)s was evaluated by means of ICP-OES. Our findings revealed that the air of these municipalities was limitedly contaminated by PTE; in fact, only Sb, Al and Mn were detected in the olive leaves collected in some of the assayed municipalities and showed a high enrichment factors (EC) manly due, probably, to the vehicular traffic emissions. Furthermore, the concentrations of the other assayed PTEs were lower than those of Sb, Al and Mn. For these reasons we suppose that their emissions in the troposphere have been and are limited, and they mainly have a crustal origin. Even if our data are very comforting for those urban area, regarded by many as one of the most contaminated one in Italy, a great environment care, in any case, is always needed. Highlights: PTEs represent a serious risk for ecosystems and human health due to their persistence and biotoxicity. Olive trees are good bioindicators to assess the air suitability at the "Land of pyres" area. The air at the "Land of pyres" area was only marginally polluted by PTE. Enrichment factors revealed anthropogenic origins for Sb, Al and Mn elements.